Violette Leduc's Feminist Flâneries - Kaliane Ung (Studies in 20th & 21st Century Literature, 2022)
Popularized by Charles Baudelaire and Walter Benjamin, the modern figure of the flâneur disrupts the pace of the city as he strolls the streets, making his way into the world through wandering and daydreaming. Assimilated to an available body to seduce, a woman walking alone does not have the same experience. However, in spite of constant interruptions in her outward and inward exploration, the flâneuse reinvents the act of walking through a form of solidarity that enables her to transcend the limits of her own body. Focusing on Violette Leduc who wrote on female sexuality in a daring way, I read the act of walking through the lens of feminist and queer theory. I argue that female flânerie is negotiated as a bodily quest with the aim of travelling with one’s gaze to reestablish female agency and cross the limits imposed by society. I study four different acts of Leduc's flânerie in Paris and the French countryside, moments that are particularly interesting because the woman queers herself to enjoy the privilege of idly wandering, liberating herself from the constraints attached to her “open” anatomy. The cis-woman’s “disidentification” happens through masquerade, daydream, and drag, until the narrator finds female solidarity in the act of traveling.
Keywords: Violette Leduc; flânerie; gender studies; queer studies; tourism